Rock mass property evaluation based on the borehole wall images taken by using an ultrasonic scanner (USS) - Ootsuka, Yasunori; Ishikawa, Takanori; Tajima, Katsuhiro; Wada, Testu; Aydan, Omer; Tokashiki, Naohiko; Sato, Tshinori; Aoyagi, Kazuhei (Journal of Nepal Geological Society, 2018)
Discontinuities, such as faults and fractures exist even in Neogene soft sedimentary rocks. These discontinuities play an important role for determination of physical, mechanical and hydraulic properties of rock mass. For geological disposal of high-level radioactive waste, these data should be obtained for designs of the layout of repository, engineered barrier system and safety assessment. Rock mass properties are important information for quantitative rock mass classification as well as for design and construction of underground facilities and assessment of safe waste disposal. Ultrasonic wave reflection intensity of the wall of the borehole drilled from bottom of East Access Shaft in Horonobe Underground Research Laboratory Center, Hokkaido, Japan, was obtained by using the ultrasonic scanner (USS). In this paper, we compared results of USS observation with core logging data including the core observation, the optical digital scanner (ODS) observation, and result of Needle Penetration Index (NPI) tests. These results indicated that ultrasonic wave reflection intensity had a good correlation with other observation results, and USS observation and NPI test are useful techniques for the determination of the detailed rock mass classification.